BIOM-43. THE GENOMIC, TRANSCRIPTOMIC, AND EPIGENOMIC LANDSCAPE OF ISOCITRATE DEHYDROGENASE WILD TYPE GLIOBLASTOMA ACROSS THE AGE CONTINUUM. (14th November 2022) - Johnson, Margaret; Bell, April; Shah, Yajas; Viets-Layng, Kayla; Mauer, Elizabeth; Xiu, Joanne; Elemento, Olivier; Glantz, Michael; Walker, Phillip; Chen, Clark; Dunbar, Erin; Fonkem, Ekokobe; et al.
Abstract: BACKGROUND: Older age is a poor prognostic factor for glioblastoma (GBM) patients. We tested whether the intrinsic molecular landscape of the tumor may contribute to this poor prognosis. METHODS: In accordance with the 2021 WHO classification scheme, we included only isocitrate dehydrogenase (IDH) wild type GBM. Based on published literature, we defined older as age > 65. RNA expression, gene amplification, tumor mutational burden (TMB) and mutational profiles were analyzed in three unique datasets: Tempus ( n = 1, 410), Caris ( n = 1, 432), and TCGA ( n = 557). Comparison were made between < 65 and ³ 65 year olds using Pearson's Chi-squared tests, Fisher's exact tests, or Wilcoxon rank-sum where appropriate. RESULTS: From our evaluable gene sets, TERT promoter mutations were more prevalent in patients ³ 65 years old (Caris 82.64 vs 77.27%, p = 0.016; Tempus 58.0 vs 49.0%, p = 0.002). There were no significant differences in PDCD1, CD274, CD3E, TNFRSF18, CD40, CD8A, TNFRSF4, CTLA4, HAVCR2, TNFSF9, CD274, or CDKN2A; PDL-1 (by IHC); dMMR/MSI-H, TMB; CDK6 amplification, EGFR amplification, EGFR, EGFRvIII, EGFR fusions, MET fusions, PTEN, TP53, or NF-1. MGMT promoter methylation (Caris data) was more common in the older group (49.73 v 34.14%, p < 0.001). TGCA data demonstrated that gene expression, TMB, and methylation did not change significantly with age. Additionally, PCOLCE2 and SLC10A4 were differentially methylated, and missense mutations, of any type, were more common in the older group (p=0.006). CONCLUSION: Despite worse survival outcomes for older patients with IDHwt GBM as compared to younger counterparts, the molecular landscape is similar at the genomic, transcriptomic and epigenomic levels. The key exception is TERT promoter mutations that are more common in older GBM patients. Poorer survival is therefore not likely to be attributable solely to intratumoral factors.